Coupling coordination and interactive relationship between population urbanization and land urbanization from the perspective of shrinking cities: a case study of Jiangsu province, China - Chen, Shao-Jun; Dai, Qi; Liu, Xiao-Yan (Frontiers in Environmental Science, 2024)
Urban contraction brings about certain impacts on the advancement of urbanization. This paper explores the coupling coordination (CCD) and geographical distribution of land urbanization (LU) and population urbanization (PU) in Jiangsu Province through a CCD model and a spatial autocorrelation model from the perspective of shrinking cities. The Panel Vector Autoregression (PVAR) model is constructed to deeply investigate the complex interaction between the PU-LU in 13 cities, 2007-2020. The study found that the PU-LU CCD in each of the above-mentioned cities shows a synergistic incremental evolution during the study period in terms of time series. In addition, in terms of spatial characteristics, the CCD of PU and LU shows significant positive global spatial autocorrelation, and the CCD of cities with high population size growth is much larger than that of cities with continuous population size. Last, there is an interactive response relationship between PU and LU. PU influences LU, however, PU itself is influenced by its own system's internal structure. The impact of PU on LU shows a positive cumulative effect of the "inverted U shape." Furthermore, this paper proposes that policies be created to ensure the coordinated growth of PU-LU. The link between floating population and construction land for cities should be established through enhancing the extent of intensive land use and reforming household registration.